2017
DOI: 10.15537/smj.2017.3.15937
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic anatomy of the lacrimal sac for dacryocystorhinostomy

Abstract: Objectives:To assist the endoscopic localization of the lacrimal sac (LS) relative to nearby landmarks.Methods:This is a descriptive prospective anatomical study. Sixteen lateral nasal walls were dissected endoscopically to identify and localize the LS between October and November 2015. Multiple measurements were obtained from the NS to the anterior and posterior walls of the LS, as well as to the middle turbinate axilla (MTA) and from the MTA to the LS borders.Results:The average distance from the NS to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…In a Taiwanese study, the lacrimal bone thickness was found to be higher in males (18). However, the reported measurements in the Taiwanese study (male, 5.8 ± 0.9 mm; female, 4.2 ± 0.8 mm) were much higher than those in other documented results (10,11,15,(19)(20)(21)(22). In our study, the thicknesses of both maxillary and lacrimal bones were higher in males at all three axial planes.…”
Section: Discussioncontrasting
confidence: 83%
“…In a Taiwanese study, the lacrimal bone thickness was found to be higher in males (18). However, the reported measurements in the Taiwanese study (male, 5.8 ± 0.9 mm; female, 4.2 ± 0.8 mm) were much higher than those in other documented results (10,11,15,(19)(20)(21)(22). In our study, the thicknesses of both maxillary and lacrimal bones were higher in males at all three axial planes.…”
Section: Discussioncontrasting
confidence: 83%
“…The top of the dacryocyst is the blind end, and the bottom is continuous with the nasolacrimal passage. Relevant studies have found that the upper part of the dacryocyst is wider than the lower part, and it is trapezoidal [46]. The dacryocyst is a bone fossa with hard bone in the front and thinner bone in the back.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the complication rate of endo-DCR in experienced hands are never higher than 2%. According to Alherabi et al 26 , several factors are responsible for the failure of endoscopic DCR, including the location of the bony ostium and its size, as well as adequate exposure and opening of the lacrimal sac. To achieve the best result, recent studies suggest the importance of opening the lacrimal sac ostium as wide as possible.…”
Section: Figure 5a and 5b Concha Bullosa Of Left Middle Turbinate (Re...mentioning
confidence: 99%